2008
DOI: 10.1302/0301-620x.90b5.19743
|View full text |Cite
|
Sign up to set email alerts
|

The use of retrievable inferior vena cava filters in orthopaedic patients

Abstract: This study was undertaken to evaluate the safety and efficacy of retrievable inferior vena cava filters in high-risk orthopaedic patients. A total of 58 patients had a retrievable inferior vena cava filter placed as an adjunct to chemical and mechanical prophylaxis, most commonly for a history of previous deep-vein thrombosis or pulmonary embolism, polytrauma, or expected prolonged immobilisation. In total 56 patients (96.6%) had an uncomplicated post-operative course. Two patients (3.4%) died in the peri-oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…7,20 Despite several studies regarding minor complications with the use of IVC filters, no complication was reported in the present study. 23,24 There is still controversy about the routine use of CT for evaluating VTE. However, simultaneous acquisition of indirect venography CT and PE-CT at a single venous infusion of contrast dye not only reduces the chance of possible side-effects by the media, but also enables precise inspection of patients' lung status.…”
Section: Discussionmentioning
confidence: 99%
“…7,20 Despite several studies regarding minor complications with the use of IVC filters, no complication was reported in the present study. 23,24 There is still controversy about the routine use of CT for evaluating VTE. However, simultaneous acquisition of indirect venography CT and PE-CT at a single venous infusion of contrast dye not only reduces the chance of possible side-effects by the media, but also enables precise inspection of patients' lung status.…”
Section: Discussionmentioning
confidence: 99%
“…Like Young et al, we believe there is very limited evidence concerning VCF outcomes when used within their currently approved indications, especially of retrievable filters. Several studies have reported on varied percentages of transient filter's mechanical complications and irretrievability when treating orthopaedic patients, especially in trauma cases 7,[32][33][34][35][36][37][38] . Fullen et al 30 reported that technical difficulties, largely mechanical, were more frequent in women and related to the small size of the jugular vein.…”
Section: Discussionmentioning
confidence: 99%
“…4 Nevertheless, it is widely believed that most filter's complications can be avoided by prompt removal: as time from implantation elapses, chances for a TED recurrence persist or may be even aggravated 5 . Consequently, retrievable filters are preferred over permanent ones nowadays, although there is a marked paucity of evidence describing their association with mechanical and hematologic complications in orthopaedic surgery [6][7] . The AAOS clinical practice guideline for preventing thromboembolic disease in patients undergoing elective hip and knee arthroplasty was unable to recommend for or against the use of filters because of inconclusive evidence 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Based on predominantly retrospective studies the authors recommended that a prophylactic IVC filter should be considered in very high-risk trauma patients, namely those who cannot receive anticoagulation because of increased bleeding risk, and those with injury patterns rendering them immobilised for a prolonged period of time (Rogers et al, 2002). Two studies since have demonstrated that temporary IVC filters can be effective in preventing pulmonary emboli in multiply injured trauma patients, and that these filters may be placed relatively simply with a low complication rate (Rosenthal et al, 2004;Strauss et al, 2008). However, filter retrieval was noted to be a common problem in both studies (Rosenthal et al, 2004;Strauss et al, 2008).…”
Section: Inferior Vena Cava Filtersmentioning
confidence: 99%